The effect of progressive muscle relaxation (P.M.R.) and mind relaxation into level of stress among student UNIMAS - Mohamad Abu, Najah Omar. (Universiti Malaysia Sarawak (UNIMAS), 2010)
This research aims to study about effect of progressive muscle and mind relaxation into level of stress among student in Faculty Science Cognitive Human Development. The main target of participant is student in department FCSHD and their number 212. Twenty participants randomly choose which 5 female and 15 is male from student FCSHD Unimas. All respondent are from third year. There were 12 Malay respondents and 8 Bumiputra such as Iban, Melanau and Bidayuh race respondent. Simple t – test has designed to evaluate hypotheses about group in level of differences in outcomes means to say the one – sample t – test in which the level of outcome for a group is compared to a known standard. The result was found that there is significant differences of stress level between before and after P.M.R technique. It also showed that there is significant differences between treat and anxiety inventory before and after P.M.R technique. Then for the mind relaxation the result found that there is significant relationship of stress level between before and after mind relaxation technique and also there is significant differences between trait and state anxiety inventory before and after mind technique.